Nancy Pelosi's Diplomatic Visit Against US-Taiwan Military Agreement Provides China Threat - Gunawan, Yordan; Mareto, Irvan (Faculty of Law, University of Jember, Indonesia, 2024)
The Chinese government opposes the planned visit of the Chair of the House of Representatives of the United States (US) Nancy Pelosi to Taiwan. Beijing said the trip would endanger the sovereignty and territorial integrity of the Bamboo Curtain state. China is known to claim Taiwan as part of its territory. But Taiwan has repeatedly stated that it is an independent state under the name of the Republic of China. Taiwan has always maintained that Beijing has never ruled it and has no right to speak on its behalf. One of China's efforts to